2012
DOI: 10.1620/tjem.228.197
|View full text |Cite
|
Sign up to set email alerts
|

Polyomavirus Reactivation in Pediatric Patients with Systemic Lupus Erythematosus

Abstract: Polyomavirus (PyV) infection usually persists without any symptoms in normal individuals. In immunocompromised patients including patients with systemic lupus erythematosus (SLE), PyV reactivation occurs with a high prevalence and can cause severe clinical complications. In this study, reactivation of six PyV [JC, BK, WU, KI, merkel cell (MC) and trichodysplasia spinulosa (TS)] was investigated in terms of prevalence, clinical implications and correlation with urine transforming growth factor (TGF)-β1 expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…This finding highlights the importance of checking both the urine and blood for BK virus infection and raises the question of BK virus tissue tropism. The BK viruria and/or viremia was transient and and the clinical findings of proteinuria, hematuria or elevated serum creatinine levels did not strongly support infection, which is similar to findings noted by Colla et al [18], Lu et al [19], and Rainthavorn et al [20]. We did not find a relationship between the incidence of thrombocytopenia and BK virus as reported by Lu et al [13].…”
Section: Discussionsupporting
confidence: 85%
“…This finding highlights the importance of checking both the urine and blood for BK virus infection and raises the question of BK virus tissue tropism. The BK viruria and/or viremia was transient and and the clinical findings of proteinuria, hematuria or elevated serum creatinine levels did not strongly support infection, which is similar to findings noted by Colla et al [18], Lu et al [19], and Rainthavorn et al [20]. We did not find a relationship between the incidence of thrombocytopenia and BK virus as reported by Lu et al [13].…”
Section: Discussionsupporting
confidence: 85%
“…Interestingly, patients with positive BKV viruria exhibited a higher incidence of thrombocytopenia and higher complement C3 levels [ 55 ]. Rainthavorn et al [ 56 ] reported that the prevalence of JCV and BKV reactivation was higher in pediatric SLE patients that in the general population. The study reported asymptomatic BKV viruria in 32 % of children with non-active SLE.…”
Section: Reviewmentioning
confidence: 99%
“…Patient series with immunosuppression due to a condition other than organ transplantations in which BKV reactivation has been evaluated have SLE (16)(17)(18), ANCA-related vasculitis (19) or multiple sclerosis (20). In a comparative study by Sundsfjord et al (16) on 44 patients with SLE and 88 healthy controls, the rate of BK viruria was significantly higher in the patients with SLE (16% vs. 0%).…”
Section: Resultsmentioning
confidence: 99%